Buckets on cable down wharf, La Brea Point, Trinidad - (:unkn) unknown (My University, 2011)
The postcard shows people walking along a pier with aerial tramway overhead.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Aerial tramways--Trinidad and Tobago; Docks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Piers--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago